2008
DOI: 10.1007/s10546-008-9294-x
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Sectional Drag Coefficient of a Group of Buildings with Packing Density

Abstract: Reynolds-averaged Navier-Stokes (RANS) simulations of turbulent flow over groups of buildings with different packing densities are reported. The results for a selected packing density are compared with direct numerical simulations (DNS) previously validated against wind-tunnel data. The present study is focused on average properties of the flow, especially on the drag coefficients, and is a first attempt to provide information on these parameters (their values are not generally known) for a range of packing de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 16 publications
3
81
1
Order By: Relevance
“…The roughness length results, in figure 8(a), closely follow the skin friction trends as a function of both the solidities, as shown in table 1. The drag-peak location herein is partially in contrast with previous studies, for which it was found at λ P ≡ λ F ≈ 0.15 (Hagishima et al 2009;Leonardi & Castro 2010;Kanda et al 2004) and λ P ≡ λ F ≈ 0.16 (Santiago et al 2008;Coceal & Belcher 2004). These differences are perhaps not surprising giving the high uncertainty in the fitting procedure which results in the visible scatter of the data for different studies in figure 8(a), even when values of similar frontal and plan solidity are considered.…”
Section: Effect Of Surface Morphology On Aerodynamic Parameterscontrasting
confidence: 99%
See 1 more Smart Citation
“…The roughness length results, in figure 8(a), closely follow the skin friction trends as a function of both the solidities, as shown in table 1. The drag-peak location herein is partially in contrast with previous studies, for which it was found at λ P ≡ λ F ≈ 0.15 (Hagishima et al 2009;Leonardi & Castro 2010;Kanda et al 2004) and λ P ≡ λ F ≈ 0.16 (Santiago et al 2008;Coceal & Belcher 2004). These differences are perhaps not surprising giving the high uncertainty in the fitting procedure which results in the visible scatter of the data for different studies in figure 8(a), even when values of similar frontal and plan solidity are considered.…”
Section: Effect Of Surface Morphology On Aerodynamic Parameterscontrasting
confidence: 99%
“…These studies include both numerical and physical experiments (Cheng & Castro 2002b;Coceal & Belcher 2004;Kanda et al 2004;Cheng et al 2007;Hagishima et al 2009;Santiago et al 2008;Leonardi & Castro 2010 among various others). Open symbols in figure 2(a) show the cases examined in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…5a), consistent with the trend reported for rigid canopies (Poggi et al 2004b;Santiago et al 2008). As suggested by DNS results of Santiago et al (2008), the instantaneous drag coefficient (C d ) for a canopy of rigid cubes is approximately a constant, and most of the variability in the mean drag coefficient ( C d ) is attributed to the contribution from the components of TKE and DKE. Removing the variability in C d caused by variability in TKE and DKE is critical for investigating the drag-wind relationships.…”
Section: Implications For the Models Of Mean Drag-wind Relationshipssupporting
confidence: 87%
“…Thirdly, the work done by the canopy drag is expected to dissipate the total kinetic energy of the flow, whereas only the mean velocity directly appears on the right-hand side of (3). Therefore C d must contain the variability associated with TKE and dispersive kinetic energy (DKE), as confirmed by direct numerical simulation (DNS) of a staggered arrangement of rigid cubes (Santiago et al 2008). Alternatively, the model of the mean canopy drag can be modified to account for the dissipation of TKE and DKE explicitly,…”
Section: Models Of Mean Canopy Drag and Traditional Estimates Of Locamentioning
confidence: 99%
See 1 more Smart Citation